Isolation and characterisation of chemical constituents from Myrmecodia Tuberosa (Rubiaceae) / Khong Heng Yen and Saidi Rasemi - Yen, Khong Hen; Rasemi, Saidi (Universiti Teknologi Mara Cawangan Sarawak, 2014)
Medicinal plants have been used for centuries as remedies for human diseases as they contain components of therapeutic value. Most of the modern medications are derived originally from ancient herbal traditions. Previous studies have revealed that Myrmecodia species isolated flavanoids as the major compounds. In addition, chemical compounds derived from Myrmecodia species also exhibited interesting biological activities, including cytotoxic, antibacterial, antidiabetic and anti-cancer. It would be interesting therefore, to identify the bioactive compounds of Myrmecodia tuberosa from Sarawak and determine their anti-diabetic and antioxidant properties. This study will be conducted on the barks of Myrmecodia tuberosa. Powdered air-dried barks samples of M. tuberosa (2-3 kg) will be extracted in methanol to yield methanol crude extracts and then will be fractionated, isolated and purified using chromatographic methods. Analyses for structural elucidations of pure bioactive compounds will involve the modern spectroscopic techniques such as NMR, FTIR and MS. All the crude extracts and pure compounds (subject to the availability) will be assayed for the anti-diabetic and antioxidant, which will be carried out based on slight modified Matsui et al. (1996) method and the 2,2-diphenyl-1-picrylhydrazyl (DPPH) respectively. The isolation and characterization of these bioactive compounds derived from the barks of Myrmecodia tuberosa will lead us to establish a chemical and biological profile of the extract for standardization and product development. The outcome of this project is a document of medicinal plants rich in bioactive compounds for further investigation for potential in drug development. Moreover, it will also provide useful information for biotechnology research and development based on government National Biotechnology Policy to develop products derived from local plants and herbs.